Ultrasound assessment of foetal head-perineum distance prior to induction of labour as a predictor of successful vaginal delivery: a prospective study from a tertiary care hospital of Rajasthan - Choudhary, Neeraj; Verma, Savitri; Gandhi, Sudha; Monga, Anuradha; Charan, Vimla; Kumari, Asha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Induction of labor (IOL) is one of the most frequent obstetric procedures require for various obstetrics indications in 13-20% of term. Traditionally success of induction has been determined by Bishop score, but this score is observer based and significant inter observer disagreements have been noted. Ultrasound can help obstetricians in counselling patients before induction of labour and explain the probability of successful induction. So in this study we did ultrasound assessment of foetal head-perineum distance prior to induction of labour as a predictor of successful vaginal delivery. Methods: All eligible women who are planned for induction of labour will undergo ultrasound assessment of foetal head–perineum distance prior to induction of labour. Transvaginal ultrasound will also be performed using ultrasound probe to measure cervical length. After the scans, prevaginal examination will be performed to assess the various components of modified Bishop score (min 0, max 10). If cervix is found unfavourable, induction of labour will be done. If patient did not go into active labour, then induction will be considered unsuccessful) or else oxytocin drip in cases where cervix is found favourable. The patients will be followed up till delivery. Results: Out of 125 patients enrolled for the study, 101 women delivered successfully vaginally and 24 had to undergo caesarean delivery. Of these 24 cases of caesarean delivery, 11 cases were excluded as the operative procedure was performed for indication not related to unsuccessful induction such as occurrence of foetal distress in labour, thick meconium-stained liquor with unfavourable cervix. The final analysis was performed from 114 subjects (101 vaginal births and 13 caesarean births). Conclusions: Transperineal fetal head–perineum distance is less painful as less time consuming and less acceptable by patients compare to Transvaginal measurement of cervical length and painful digital examination for bishop score.